2019
DOI: 10.1101/641878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genotype-dependent and non-gradient patterns of RSV gene expression

Abstract: 30Respiratory syncytial virus (RSV) is a nonsegmented negative-strand (NNS) RNA 31 virus and a leading cause of severe lower respiratory tract illness in infants and the 32 elderly. Transcription of the ten RSV genes proceeds sequentially from the 3' promoter 33 and requires conserved gene start (GS) and gene end (GE) signals. Previous studies 34 using the prototypical GA1 genotype Long and A2 strains have indicated a gradient of 35 gene transcription. However, recent reports show data that appear inconsist… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
0
8
1
Order By: Relevance
“…and genotype-dependent transcription in RSV and Ebola (22,23). During transcription, using a single promoter in the 3' leader region (Le) of the genome, the polymerase initiates and terminates the mRNA transcription in response to the gene start (GS) and gene end (GE) signals.…”
Section: Downloaded Frommentioning
confidence: 99%
“…and genotype-dependent transcription in RSV and Ebola (22,23). During transcription, using a single promoter in the 3' leader region (Le) of the genome, the polymerase initiates and terminates the mRNA transcription in response to the gene start (GS) and gene end (GE) signals.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Typically, the RdRP produces a gradient level of viral mRNAs with the attenuation of the downstream mRNAs at each gene junction (71,72). Recent studies showed the non-gradient and genotype-dependent transcription in HRSV and EBOV, suggesting alternative gene expression strategies (73,74) (Fig. 1, lower part).…”
Section: Fig 1)mentioning
confidence: 99%
“…A cis-acting sequence gene end (GE) signals polyadenylation and termination; (iii) the polymerase stays on the template, reinitiates and caps the downstream mRNAs, and terminates and polyadenylates the upstream mRNAs in response to GS and GE signals of downstream genes (26,27); (iv) Like other Mononegavirales, the attenuation of the downstream mRNA occurs at each gene junction for most genes (25). Recent studies indicated the existence of nongradient and genotypedependent transcription in RSV, suggesting the possibility of such nongradient gene expression in other Mononegavirales (34,36). Through this process of sequential attenuation of transcription, L produces ten viral mRNAs with appropriate ratios (32) (Fig.…”
Section: Rna Synthesis Of Pneumoviridaementioning
confidence: 99%